Post cryosurgical rehabilitation of ear chondroma. Case from practice - Таgunova Іrіna; Аndreev Alexander; Gushcha, Sergey; Plakida, Alexander; Zukow, Walery (Journal of Education, Health and Sport, 2023)
A typical place of localization of chondroma is the cartilaginous tissue of the auricle, which rarely develops and most often in people at a young age. Existing treatment methods are effective and widespread, however, any injury to the tumor accelerates its growth. Therefore, significant development of chondromas is observed after a trial excision or incomplete removal. Cryosurgical treatment refers to gentle, less traumatic methods. Тhe authors describe a case from practice: removal of the chondroma of the outer ear using a СAO-2 cryoapparatus with an individual polyethylene cap, which allows for accelerating and simplifying the process of thawing and re of the instrument. This intervention is outpatient and does not require special preparation. Taking into account the undesirable complications after cryotherapy (swelling, pain due to increased tissue turgor, local deterioration of blood circulation) on the one hand, and taking into account the antitoxic, calming, relaxing, and analgesic effect of magnesium on the body as a whole, the authors used balneotherapy in the form of a course of applications with a natural balneological agent with a high content of magnesium chloride on the zone of cryotherapy, as well as its drinking course consumption. The observation showed that the intervention using a cryoapplicator is a gentle method, slightly damaging the surrounding tissues, minimizing the possibility of intraoperative bleeding, allowing to accelerate the operation process and healing time, and, accordingly, reducing the patient’s incapacity for work. Applying the results in clinical practice will significantly reduce the likelihood of deformation of the outer ear and maintain its primary functions.